2004
DOI: 10.1063/1.1738513
|View full text |Cite
|
Sign up to set email alerts
|

A widely tunable refractive index in a nanolayered photonic material

Abstract: Public reporting burden for the collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing the collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing this burden, to Washington Headquarters Services, Directorate for Information Operations and R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 13 publications
0
24
0
Order By: Relevance
“…[1±3] Single metallic films [4±11] and multilayered metal films, [10,12,13] metal-ceramic layered composites, [14±25] ceramic-ceramic layered composites [26,27] and polymer nanolayered composites [28,29] have been investigated. Improved hardness, wear resistance, toughness, and/or oxidation resistance may be achieved through careful selection and optimization of layered materials at the nanoscale.…”
Section: Introductionmentioning
confidence: 99%
“…[1±3] Single metallic films [4±11] and multilayered metal films, [10,12,13] metal-ceramic layered composites, [14±25] ceramic-ceramic layered composites [26,27] and polymer nanolayered composites [28,29] have been investigated. Improved hardness, wear resistance, toughness, and/or oxidation resistance may be achieved through careful selection and optimization of layered materials at the nanoscale.…”
Section: Introductionmentioning
confidence: 99%
“…Disturbing light reflection from computer monitors, television screens and LCD displays are further examples from daily experience. Antireflection coatings are most frequently single or multilayer interference structures with alternating high and low refractive indices (Walheim et al 1999) (Sandrock et al 2004) (Xi et al 2007). Reflection is reduced for normal incidence due to destructive interference of reflected light from the layer-substrate and the air-layer interface.…”
Section: Antireective Surfaces -The "Moth Eye" Principlementioning
confidence: 99%
“…Caseri showed that particle size should be reduced to below ~50 nm in a nanocomposite in order maintain transparency with relaxed restrictions on refractive index matching (7). In this size regime, with characteristics lengths much smaller than the incident wavelengths, light passing through the interphase will be less susceptible to scattering, and the region will behave as an optically homogeneous material with a refractive index (n i ) that is essentially the volumeaveraged refractive index of its constituents (8). Therefore, if the nanocomposite interphase is composed of the same glass and polymer as the conventional composite with refractive indices n g and n p , respectively, then…”
Section: Our Approachmentioning
confidence: 99%